(untitled) (UUM Journal of Legal Studies, 2022)
This study investigated consumer rights protection in Indonesia on price gouging during the Covid-19 outbreak. This research employed normative law with a statutory approach and an analytic approach. The Consumer Protection Act, the Anti-Monopoly and Unfair Business Law, the Civil Law, and the Trade Law were the primary sources. Meanwhile, the supporting sources included books, journals, and articles on the internet. The object of research focused on consumer protection from price gouging for necessities during the Covid-19 pandemic. The results revealed that unhealthy business competition during the pandemic have harmed Indonesian people in fulfilling their basic needs to stay healthy. Goods in urgent demand such as masks and hand-sanitizers have a lower consumer buying interest due to the unfair selling power set by several business actors. The Indonesian government has prohibited business actors from deliberately gouging product prices during the Covid-19 pandemic. It has also played a central role in establishing and enforcing civil and criminal laws on business actors who set unreasonably high prices, resulting in consumer economic difficulties amid the outbreak of Covid-19.